Activity of the European Court of Human Rights and Its Impact on Ukraine's Criminal Justice Policy - FRIS, Pavlo L.; MYKYTYN, Yurii I.; KRUL, Sviatoslav M.; SHPILIAREVYCH, Viktoriia V. (Journal of Advanced Research in Law and Economics; Vol 10 No 3 (2019): JARLE Vol X Issue 3(41) Summer 2019DO - 10.14505//jarle.v10.3(41).09, 2019)
The relevance of the study is due to the fact that one of the main directions of Ukraine's domestic policy is ensuring the rights and freedoms of citizens through national and international mechanisms for their protection. In this context, the article aims to analyze the activities of the European Court of Human Rights as an effective international mechanism for the protection of human rights and freedoms and its impact on the criminal law of Ukraine as an integral part of crime prevention policy. Leading approach to the study of this problem is the method of generalization of legal theory and practice that has afforded revealing impact of the activities of the European Court of Human Rights on the criminal law of Ukraine. The materials of the paper imply the practical significance for the university teachers of the legal specializations.